## y = 2x + 3 y = -2x + 15 Can you please explain how to get the answer.

Question

y = 2x + 3
y = -2x + 15

in progress 0
1 week 2021-10-05T05:22:45+00:00 2 Answers 0 and Step-by-step explanation:

Given: …………………….. equation i …………………… equation ii

since y is equals to the two functions , we can equate the two values of y . That is , equate equation i and ii , we have Add to both sides , we have  subtract 3 from both sides , we have divide both sides by 4 , then substitute into equation i to get the value of y , that is   Therefore : and x =3 and y = 9

Step-by-step explanation:

This is a simultaneous equation

y = 2x + 3      is equation 1

y = -2x + 15    is equation 2

Using the elimination method, we will add the two equations together

Then, we will have

2y = 18

Note that y+y =2y, 2x+(-2x) = 0 and 3+15 =18

y = 18/2  (dividing both sides by 2)

Therefore, y = 9.

Since we know the value of y, we can substitute 9 for y in any of the equation.

Lets substitute 9 for y in equation 1, we will have

9 = 2x + 3

collecting like the like terms

9 – 3 = 2x

6 = 2x

if we divide both sides by the coefficient of x, which is 2, we will have

x = 6/2

x = 3

Therefore x = 3 and y = 9